The influence of brand image on brand loyalty: a study at Telekom Malaysia Berhad / Noor Hazida Abdul Halim - Abdul Halim, Noor Hazida (2011)
The aim of this study was to examine the component of brand image that influence brand loyalty in Telekom Malaysia Berhad Melaka. In this study, researcher has chosen organization as the component of brand image since organization has the most influence towards brand equity in services than others variables. The researcher also found that brand loyalty is the main component in brand equity. The components of organization include reputation, service offering, contact personnel, corporate identity and physical environment. This study also was conducted to identify what are the most preferred factors that influence brand loyalty in Telekom Malaysia Berhad. Moreover, questionnaires had been used in order to get feedback from customers. Researcher had distributed 75 questionnaires to Telekom Malaysia customers at area of Ayer Keroh Melaka. The data collected was then tested on its Frequency and Pearson’s r test of correlation and then further analyzed using Reliability analysis and regression analysis was used to test the hypotheses in this study. The findings of this paper suggest that not all the factors are significant factors for explaining brand loyalty in Telekom Malaysia Berhad. Only reputation has been selected as the most significant factors for explaining brand loyalty in Telekom Malaysia Berhad. Based from the results obtained in this study, researcher suggests some recommendations that can help Telekom Malaysia Berhad to assist the current and future good services